The Influence of Foreign Directors and Chinese Directors in Indonesia on Companies Value in the Oil, Gas, and Coal Sub-Sector Listed on the Indonesia Stock Exchange for the 2021-2023 Period - Dara anggraini Dara anggraini; Cut Fitrika Syawalina Cut Fitrika Syawalina; Desy Purnamasari Desy Purnamasari (Outline Publisher, 2026)
Purpose: This research focuses on understanding the extent to which the presence of foreign directors and those of Chinese ethnicity in Indonesian companies particularly in the oil, gas and coal sub-sectors influences company value. The focus is on companies listed on the Indonesia stock exchange between 2021 and 2023. Methods: The analysis uses a panel data regression model with data processing conducted through EViews 13 software. Results: The study finds that, collectively, the presence of foreign and meanwhile directors of Chinese ethnicity actually show the opposite impact namely negative impact on company value. When tested individually foreign directors show a positive impact whereas Chinese ethnic directors exhibit a negative influence on firm value. Conclusions: These findings emphasize the crucial role of board diversity in shaping firm value and highlight its importance as a strategic benchmark for future corporate growth. Value/Originality: This study offers new insights into how diversity within boards can impact firm value by highlighting the roles played by directors from both foreign and chinese backgrounds. The results broaden the discussion in corporate governance literature, showing that diverse director backgrounds can provide strategic advantages for Indonesian companies.